2014
DOI: 10.1007/s11427-013-4604-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabinoid receptor type 2 on endogenous myocardial regeneration by activating cardiac progenitor cells in mouse infarcted heart

Abstract: Cannabinoid receptor type 2 (CB 2 ) activation is recently reported to promote proliferation of some types of resident stem cells (e.g., hematopoietic stem/progenitor cell or neural progenitor cell). Resident cardiac progenitor cell (CPC) activation and proliferation are crucial for endogenous cardiac regeneration and cardiac repair after myocardial infarction (MI). This study aims to explore the role and possible mechanisms of CB 2 receptor activation in enhancing myocardial repair. Our results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…In response to chronic pressure the -actinin-binding muscle LIM protein (MLP) translocates from the cytoplasm to the nucleus. MLP in the nucleus stimulates myogenic differentiation through binding to the muscle-specific transcription factor MyoD, which enhances transcriptional activity of the downstream targets (Wang et al, 2014;. In our previous study, Kindlin-2 translocates into nucleus to form a tripartite complex with active -catenin and TCF4 and regulates myogenic regulatory factor myogenin via a canonical Wnt/-catenin signaling (Wu et al, 2015;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In response to chronic pressure the -actinin-binding muscle LIM protein (MLP) translocates from the cytoplasm to the nucleus. MLP in the nucleus stimulates myogenic differentiation through binding to the muscle-specific transcription factor MyoD, which enhances transcriptional activity of the downstream targets (Wang et al, 2014;. In our previous study, Kindlin-2 translocates into nucleus to form a tripartite complex with active -catenin and TCF4 and regulates myogenic regulatory factor myogenin via a canonical Wnt/-catenin signaling (Wu et al, 2015;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…We tested the lower dose of 4 mg·kg −1 and found this lower dose caused no significant weight change but tended to improve mice survival (Figure S1a). For AM1241, a previous study used the dose of 20 mg·kg −1 in an infarcted mouse model (Wang et al, ). We initially tested this dose and found that the beneficial effects of AM1241 at this dose were not significant.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Zhi et al describes that wortmannin significantly decreases the expression of collagen type I in adult rat cardiac fibroblasts (Zhi, et al, 2013). On the other hand, Wang et al show that wortmannin cancels the effects of cannabinoid receptor type 2 agonist including improving cardiac function, decreasing fibrosis and reducing inflammatory cytokine secretion and oxidative stress in a mouse model with infarcted heart (Wang, et al, 2014). Lastly, Zhang and others also identify that wortmannin abolishes zinc's anti-fibrotic capacity in a rat kidney tubular epithelial cell line .…”
Section: Highlighting Anti-fibrotic Drug Candidatesmentioning
confidence: 99%